Assessment of enamel remineralising capability of three different remineralising agents using vicker’s surface microhardness test. - DR. SHYAMBHAVI SRIVASTAVA; DR. POOJA KABRA; DR.EKTA CHOUDHARY (International Journal of Pharma and Bio Sciences, 2019)
Any clinical research merit is granted by the advancement it promises to bring to the society, much towards the same goal this study provides modalities for a caries-free world by comparing the commercially available remineralising agents. The aim of this study is to evaluate and compare the enamel remineralisation potential of three different remineralising agents; namely:- Elsenz` tooth creme`, GC tooth mousse plus and Sensodyne repair and protect.50 freshly extracted teeth were cleaned and stored in a hydrated state in 10% FORMALIN. The samples were autoclaved for a cycle for 40 minutes to get rid of bacterial residues. Enamel samples were prepared by slicing the teeth mesio-distally into buccal and lingual halves, using a diamond disc fixed on a straight handpiece. The buccal halves were used for the microhardness study. The samples were divided into five groups of 10 samples each. Vicker’s microhardness readings were calculated before demineralisation, after demineralisation, 15 days after demineralisation and remineralisation treatment and 30 days after demineralisation and remineralisation treatment.Though an in vitro study, this study paves the pathway for detailed clinical research work which can be conducted to establish a gold standard protocol to achieve maximum benefit from the available remineralising agents. With the in vitro results obtained from this study it can be concluded that, ELSENZ` TOOTH CREME` exhibited a significantly greater potential for remineralisation of demineralised enamel lesions. However, it is important to keep in mind that remineralisation process analysed outside the oral cavity will be different when compared to conditions occurring inside the oral cavity.